2013
DOI: 10.1002/smll.201301595
|View full text |Cite
|
Sign up to set email alerts
|

Thymine and Adenine Tetrads Formed on Anisotropic Metal Surfaces

Abstract: The interplay of the Au(110) surface and alkyl-substituted DNA bases induces reorganization of the surface with parallel atomic grooves, while the enhanced surface anisotropy constrains the substituent alkyl chains along the grooves. Every four molecules are bound together through H-bonds while further possible H-bonds are prohibited by either the alkyl chains or the groove borders, resulting in separated tetrad structures located in the grooves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…First, we built up structural models of the triangular clusters based on the canonical form of the Umolecule;however, we identified that the most stable parallelogrammic model did not agree with the experimental configuration as illustrated in Figure S3. As it is known that the nucleobases can undergo tautomerization on surfaces, [39][40][41] we then re-built our models taking into account the non-canonical forms of the Umolecule.A fter an extensive structural search and comparison with STM images,w ei dentified the energetically favorable models of the triangular and parallelogrammic clusters,which were overlaid on the corresponding simulated STM images ( Figure 1e); good agreements are achieved when comparing them with the experimental morphologies and dimensions. Theoptimized models showed that the triangular cluster was formed by three Umolecules coordinating to three Ni atoms, and that the parallelogrammic cluster was formed by two homochiral triangular clusters linked together through double NÀH···O hydrogen bonds.Interestingly,wefound that the two dim molecules mentioned above are just the ones that are involved in the formation of hydrogen bonds.W ethus believe that the change in apparent heights of molecules 1a nd 2 ( Figure 1c,d)s hould be attributed to the corresponding change in their molecular adsorption configurations upon hydrogen-bond formation.…”
Section: Angewandte Communicationsmentioning
confidence: 99%
“…First, we built up structural models of the triangular clusters based on the canonical form of the Umolecule;however, we identified that the most stable parallelogrammic model did not agree with the experimental configuration as illustrated in Figure S3. As it is known that the nucleobases can undergo tautomerization on surfaces, [39][40][41] we then re-built our models taking into account the non-canonical forms of the Umolecule.A fter an extensive structural search and comparison with STM images,w ei dentified the energetically favorable models of the triangular and parallelogrammic clusters,which were overlaid on the corresponding simulated STM images ( Figure 1e); good agreements are achieved when comparing them with the experimental morphologies and dimensions. Theoptimized models showed that the triangular cluster was formed by three Umolecules coordinating to three Ni atoms, and that the parallelogrammic cluster was formed by two homochiral triangular clusters linked together through double NÀH···O hydrogen bonds.Interestingly,wefound that the two dim molecules mentioned above are just the ones that are involved in the formation of hydrogen bonds.W ethus believe that the change in apparent heights of molecules 1a nd 2 ( Figure 1c,d)s hould be attributed to the corresponding change in their molecular adsorption configurations upon hydrogen-bond formation.…”
Section: Angewandte Communicationsmentioning
confidence: 99%
“…Surface‐supported molecular self‐assembly of organic molecules has attracted broad scientific and technological interests and therefore, been extensively investigated during the past two decades, both in liquid and vacuum . Generally speaking, self‐assembled molecular structure relies on a subtle balance between intermolecular (molecule–­molecule and molecule–solvent) and interfacial (molecule–substrate and solvent–substrate) interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Purity and identity are confirmed by 1 H and 13 C NMR spectroscopy, mass spectrometry, elemental analysis, and FTIR spectroscopy (Figures S2-S5). The 1 : 3 supermesogen M 13 with adenine derivative 4 [35] was assembled in DCM and freeze dried from benzene (see experimental section and Supporting Information). All materials were heated to the LC phase prior to their LC studies in order to eliminate preparation and thermal history.…”
Section: Synthesismentioning
confidence: 99%